2002
DOI: 10.1074/jbc.m106671200
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Protein A Inhibits Peptidoglycan-induced Tumor Necrosis Factor-α Secretion in U937 Cells and Alveolar Macrophages by Direct Interaction with Toll-like Receptor 2

Abstract: Pulmonary surfactant protein A (SP-A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
130
0
4

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 162 publications
(143 citation statements)
references
References 55 publications
9
130
0
4
Order By: Relevance
“…44 In brief, glycosylated and deglycosylated sTLR4 proteins (2 mg) were electrophoresed on a 13% polyacrylamide gel in The binding of MBL to sTLR4 was also examined using microtiter wells. sTLR4 or HSA (10 mg/ml, 50 ml/well) was coated onto microtiter wells, which were then incubated with 10 mM Hepes buffer (pH 7.4) containing 0.15 M NaCl, 5 mM CaCl 2 and 5 mg/ml bovine serum albumin (buffer C) to block nonspecific binding.…”
Section: Analyses Of Binding Of Mbl To Stlr4mentioning
confidence: 99%
“…44 In brief, glycosylated and deglycosylated sTLR4 proteins (2 mg) were electrophoresed on a 13% polyacrylamide gel in The binding of MBL to sTLR4 was also examined using microtiter wells. sTLR4 or HSA (10 mg/ml, 50 ml/well) was coated onto microtiter wells, which were then incubated with 10 mM Hepes buffer (pH 7.4) containing 0.15 M NaCl, 5 mM CaCl 2 and 5 mg/ml bovine serum albumin (buffer C) to block nonspecific binding.…”
Section: Analyses Of Binding Of Mbl To Stlr4mentioning
confidence: 99%
“…When sTLR2 or sCD14 was incubated without iPGN, none of them was sedimentable. When surfactant protein A, which does not bind to iPGN (34), was used as a negative control, iPGN failed to cosediment this protein.…”
Section: Recombinantmentioning
confidence: 99%
“…In the last few years, we have demonstrated that SP-A interacts with the pattern recognition receptors CD14 and Toll-like receptor (TLR)-2, and modulates the immune response to bacterial components [7][8][9]. The binding of SP-A to TLR4 is under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…SP-A has been reported to bind to various spectra of microorganisms and enhance phagocytosis by alveolar macrophages [5,6]. SP-A also modulates the cellular responses to microorganisms via its direct interactions with the pattern recognition receptors [7][8][9]. Animals lacking SP-A exhibit reduced bacterial clearance and elevated pulmonary inflammation in response to microbial challenge [10][11][12].…”
Section: Introductionmentioning
confidence: 99%